2016
DOI: 10.1371/journal.pone.0158488
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Chloroplast Genome of Ye-Xing-Ba (Scrophularia dentata; Scrophulariaceae), an Alpine Tibetan Herb

Abstract: Scrophularia dentata is an important Tibetan medicinal plant and traditionally used for the treatment of exanthema and fever in Traditional Tibetan Medicine (TTM). However, there is little sequence and genomic information available for S. dentata. In this paper, we report the complete chloroplast genome sequence of S. dentata and it is the first sequenced member of the Sect. Tomiophyllum within Scrophularia (Scrophulariaceae). The gene order and organization of the chloroplast genome of S. dentata are similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Similar to the SSRs, D . insignis contained a lower number of repeat elements compared with other plants 34 , 35 . The presence of these repeats indicated that the locus was a crucial mutation hotspot in the genome because the repeat sequences led to sequence variations and genome rearrangements due to the slipped-strand mispairing and improper recombination 36 .…”
Section: Resultsmentioning
confidence: 74%
“…Similar to the SSRs, D . insignis contained a lower number of repeat elements compared with other plants 34 , 35 . The presence of these repeats indicated that the locus was a crucial mutation hotspot in the genome because the repeat sequences led to sequence variations and genome rearrangements due to the slipped-strand mispairing and improper recombination 36 .…”
Section: Resultsmentioning
confidence: 74%
“…roxburghii ( KX768420 ) and most divergent from that of P. persica ‘Nemared’. Overall, the results revealed SC regions to be more divergent than IR regions, with higher divergence being observed in non-coding regions than in coding regions, which is a common phenomenon in the chloroplast genomes of angiosperms ( Yao et al, 2015 ; Ni et al, 2016 ; Asaf et al, 2016 ). The coding regions with marked differences include the ycf1 , matK and psaI genes.…”
Section: Resultsmentioning
confidence: 86%
“…Out of the 49 repeats, 34 repeats (69.4%) were 30–39 bp long, 11 repeats (22.4%) were 40–49 bp long, four repeats (8.2%) were 50–59 bp long, and the longest repeat was 58 bp. Generally, repeats were mostly distributed in noncoding regions [ 32 , 33 ]; however, 53.1% of the repeats in the F. suspensa cp genome were located in coding regions (CDS) ( Figure 3 A), mainly in ycf2 ; similar to that of S. dentata and S. takesimensis [ 34 ]. Meanwhile, 40.8% of repeats were located in intergenic spacers (IGS) and introns, and 6.1% of repeats were in parts of the IGS and CDS.…”
Section: Resultsmentioning
confidence: 99%